36‐2: Invited Paper: Lasers, Lamps, or Phosphors – Choices for the Future of Digital Cinema. Issue 1 (2nd June 2017) - Perkins, Michael; Koebel, Alen
Abstract : The first generation of digital‐cinema projectors has now been deployed into the majority of movie theaters around the world. The illumination technology used for that first generation was xenon lamps. When that choice was made xenon was the only viable technology that could achieve digital cinema's goals. Today, cinema has a new set of challenges and a new set of technologies to choose from. Now that laser and laser‐phosphor are mainstream illumination technologies cinema‐projection engineers have an entirely new set of design decisions to make.